2017
DOI: 10.1111/desc.12550
|View full text |Cite
|
Sign up to set email alerts
|

Verbal–spatial IQ discrepancies impact brain activation associated with the resolution of cognitive conflict in children and adolescents

Abstract: Verbal-spatial discrepancies are common in healthy individuals and in those with neurodevelopmental disorders associated with cognitive control deficits including: Autism Spectrum Disorder, Non-Verbal Learning Disability, Fragile X, 22q11 deletion, and Turner Syndrome. Previous data from healthy individuals suggest that the magnitude of the difference between verbal IQ (VIQ) and performance IQ (PIQ) scores (the VIQ>PIQ discrepancy) is associated with reduced thickness in frontal and parietal cortices (inferior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Those findings are consistent with a recent metaanalysis indicating a discrepancy between higher verbal and lower performance IQ scores in adult patients with OCD [18], which could be explained by their poorer processing speed negatively affecting the performance IQ scores [18,85,86]. Previous investigations have indicated that such discrepancy is associated with reduced motor competence among preschoolers [87] and functional neuroimaging-detected alterations during cognitive conflict resolution among children and adolescents [88]. In this regard, the appropriate school environment has reportedly contributed to improvements in the Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Those findings are consistent with a recent metaanalysis indicating a discrepancy between higher verbal and lower performance IQ scores in adult patients with OCD [18], which could be explained by their poorer processing speed negatively affecting the performance IQ scores [18,85,86]. Previous investigations have indicated that such discrepancy is associated with reduced motor competence among preschoolers [87] and functional neuroimaging-detected alterations during cognitive conflict resolution among children and adolescents [88]. In this regard, the appropriate school environment has reportedly contributed to improvements in the Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Left parahippocampal gyrus (BA 34) activation supports memory processing (Grasby et al, 1992;Svoboda and Levine, 2009). Activation of BA 9 with BA 44, 45, precentral (in frontal) precuneus, middle temporal, hippocampus and amygdala constitute the conflict-resolution network (Margolis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Higher BOLD activity of left anterior cingulate in dyslexic group suggests conflict in feedback loop (Posner and DiGirolamo, 1998), where the decreased activity (interface) of right frontal cortex and anterior cingulate contribute to optimal attentional vigilance and conflict resolution (Margolis et al, 2018;Parasuraman, Warm, See, 1998) (visuospatial model; figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that a discrepancy between verbal and nonverbal IQ occurs more frequently among children with ASD than in typically developing children (Ankenman et al, 2014; Coolican et al, 2008; Joseph et al, 2002; Nowell et al, 2015), suggesting that IQ discrepancies may be an important characteristic of ASD. Indeed neural correlates of IQ discrepancies have been identified in healthy individuals (Margolis et al, 2013, 2018). Additionally, studies suggest that differences between verbal and visual–spatial reasoning may be under genetic control (Chapman et al, 2011; Copet et al, 2010).…”
Section: Introductionmentioning
confidence: 99%